2021
DOI: 10.1111/tri.14156
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of pregnancy outcomes in Dutch kidney recipients with and without calcineurin inhibitor exposure: a retrospective study

Abstract: Within pregnancies occurring between 1986 and 2017 in Dutch kidney transplant recipients (KTR), we retrospectively compared short-term maternal and foetal outcomes between patients on calcineurin inhibitor (CNI) based (CNI+) and CNI-free immunosuppression (CNIÀ). We identified 129 CNI+ and 125 CNIÀ pregnancies in 177 KTR. Demographics differed with CNI+ having higher body mass index (P = 0.045), shorter transplant-pregnancy interval (P < 0.01), later year of transplantation and -pregnancy (P < 0.01). Serum cre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…The PARTOUT network investigated pregnancy outcomes stratified per use of CNIs earlier. 37 Therefore, we provide only an overview of baseline characteristics and outcomes of CNI use and a compact prediction analysis. Likewise, the influence of pregnancy on graft loss was earlier investigated and therefore only concisely investigated in this study.…”
Section: Study Endpointsmentioning
confidence: 99%
See 1 more Smart Citation
“…The PARTOUT network investigated pregnancy outcomes stratified per use of CNIs earlier. 37 Therefore, we provide only an overview of baseline characteristics and outcomes of CNI use and a compact prediction analysis. Likewise, the influence of pregnancy on graft loss was earlier investigated and therefore only concisely investigated in this study.…”
Section: Study Endpointsmentioning
confidence: 99%
“…Although the intuitive relationship between adverse pregnancy outcomes and graft loss can be seen, it does not prove to be a predictor for graft loss on its own. Koenjer et al 37 investigated the influence of CNIs on pregnancy outcomes and found no significant adverse outcomes. However, there is a time effect leading to bias because of the introduction of CNIs only in the 1990s and mostly women with good kidney function getting pregnant at that time.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…97 Calcineurin inhibitor toxicity maybe confused with pre-eclampsia as both cause graft dysfunction, thrombotic microangiopathy, and hypertension. 79,98 Tacrolimus levels are difficult to interpret in pregnancy because of the change in the free versus bound tacrolimus ratio. 99 Whole blood tacrolimus levels fall in the second trimester.…”
Section: Outcomes In Transplanted Womenmentioning
confidence: 99%
“…79 Clinicians may escalate dosing in response, leading to third trimester blood pressure and creatinine creep which may be diagnosed as preeclampsia and precipitate early delivery, although high preterm delivery rates have been observed irrespective of calcineurin inhibitor use. 98 Finally, clinician reluctance to progress with pregnancy in later gestation (where risks of continuing pregnancy outweigh risks of early delivery) may drive preterm birth. Regardless, women and clinicians should anticipate possible preterm delivery and undertake shared decision-making about timing of delivery.…”
Section: Outcomes In Transplanted Womenmentioning
confidence: 99%
See 1 more Smart Citation